2019
DOI: 10.1038/s41591-018-0337-7
|View full text |Cite
|
Sign up to set email alerts
|

Neoadjuvant anti-PD-1 immunotherapy promotes a survival benefit with intratumoral and systemic immune responses in recurrent glioblastoma

Abstract: Glioblastoma is the most common primary malignant brain tumor in adults and associated with poor survival. The Ivy Foundation Early Phase Clinical Trials Consortium conducted a randomized, multi-institution clinical trial to evaluate immune responses and survival following neoadjuvant and/or adjuvant therapy with pembrolizumab in 35 patients with recurrent, surgically resectable glioblastoma. Patients who were randomized to receive neoadjuvant pembrolizumab, with continued adjuvant therapy following surgery, h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
810
2
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 1,027 publications
(887 citation statements)
references
References 79 publications
16
810
2
2
Order By: Relevance
“…18 In other trial arms exploring combinations of nivolumab with ipilimumab, the response rate was a disappointing 7%. [20][21][22] Although acute ICI sensitivity of tumors with a high mutation burden, because of mismatch repair deficiency has been described, 23,24 recent data suggest that only 3.5% of primary or recurrent glioblastoma patients had a high somatic tumor mutation burden and so may benefit from ICI therapy. [20][21][22] Although acute ICI sensitivity of tumors with a high mutation burden, because of mismatch repair deficiency has been described, 23,24 recent data suggest that only 3.5% of primary or recurrent glioblastoma patients had a high somatic tumor mutation burden and so may benefit from ICI therapy.…”
Section: Standard Treatment and Prognosismentioning
confidence: 99%
See 1 more Smart Citation
“…18 In other trial arms exploring combinations of nivolumab with ipilimumab, the response rate was a disappointing 7%. [20][21][22] Although acute ICI sensitivity of tumors with a high mutation burden, because of mismatch repair deficiency has been described, 23,24 recent data suggest that only 3.5% of primary or recurrent glioblastoma patients had a high somatic tumor mutation burden and so may benefit from ICI therapy. [20][21][22] Although acute ICI sensitivity of tumors with a high mutation burden, because of mismatch repair deficiency has been described, 23,24 recent data suggest that only 3.5% of primary or recurrent glioblastoma patients had a high somatic tumor mutation burden and so may benefit from ICI therapy.…”
Section: Standard Treatment and Prognosismentioning
confidence: 99%
“…19 In three recently reported studies of neoadjuvant anti-PD1 therapy in recurrent glioblastoma patients, although clinical responses were lacking, evidence on surgical resection specimens of persistent T-cell inflammation and pro-inflammatory cytokine profiles tended to favor an improved prognosis and may suggest a rationale for ICI use in conjunction with CAR-T cell therapy. [20][21][22] Although acute ICI sensitivity of tumors with a high mutation burden, because of mismatch repair deficiency has been described, 23,24 recent data suggest that only 3.5% of primary or recurrent glioblastoma patients had a high somatic tumor mutation burden and so may benefit from ICI therapy. 2 Notwithstanding promising case reports, [25][26][27][28] formal testing of the sensitivity of this group of patients to ICI therapy is awaited.…”
Section: Immune Checkpoint Inhibitor (Ici) Therapymentioning
confidence: 99%
“…Several preclinical studies have shown benefit in blocking PD‐1 or CTLA‐4 in murine glioma models. Importantly, two recent clinical reports have shown benefit for neoadjuvant anti‐PD‐1 immunotherapy in promoting survival and modifying the TME in glioma patients. These promising reports suggest that blocking PD‐1 changes the TME and could synergize with CAR T therapy in improving the survival of glioma patients.…”
Section: Car T Cells and The Suppressive Microenvironment Of Brain Tumentioning
confidence: 99%
“…Several preclinical studies have shown benefit in blocking PD- 1 181 or CTLA-4 182 in murine glioma models. Importantly, two recent clinical reports have shown benefit for neoadjuvant anti-PD-1 immunotherapy in promoting survival 20 and (IL13Rα2-CAR T + Nivolumab). Although, the clinical impact of CAR-T cells combined with checkpoint inhibitors in GBM is still unknown, results from these trials will provide important information regarding safety, feasibility, and potential anti-tumor activity.…”
Section: Combination Therapies To Augment Car T Cell Functionmentioning
confidence: 99%
See 1 more Smart Citation